Spontaneous Regression of a Thymoma with Mild Pleural Effusion: A Case Report - Alnassar, Abdulaziz (International Journal of Innovative Research in Medical Science, 2023)
Introduction: Spontaneous regression of a thymoma is an unusual and rare phenomenon witnessed across the field of thoracic medicine. Presentation of Case: A 33-year-old man presented with persistent right shoulder pain and shortness of breath which started 1 month prior to hospital visit. Computed tomography of the chest was done which showed an 11.0 cm anterior mediastinal mass with bilateral pleural effusion. The man refused surgery and was discharged without any treatment. 7 months later upon evaluation, the mass had regressed more than 70% of its size with subsequent disappearance of the pleural effusion. Right thoracoscopic thymectomy was performed safely without complications. Post thymectomy, the surgical pathology report and analysis of the specimen was consistent with the diagnosis of thymoma. Clinical Discussion: Our reported case is an unusual example of a large thymoma undergoing spontaneous regression over time without any therapy provided. Previous studies have reported similar phenomena with limited insight towards the understanding of such an event. Thymomas are eventually managed by surgical resection which remains the preferred modality of treatment, most commonly via thoracoscopy consistent with our case along with past reports. Conclusion: Spontaneous regression of thymomas is widely unwitnessed in practice, thus, recognition of this rare occurrence could provide further insight in disease outcomes.